Bioprospecting For Bacterial Endophytes Associated With Zingiberaceae Family Rhizomes In Sibolangit Forest, North Sumatera - mamangkey, Jendri; Lucas William Mendes; Mada Triandala Sibero; Pilidai Endorina Nadapdap (Publisher Cv. Inara, 2020)
The present study was conducted aiming to isolate and characterize endophytic bacterial isolates with antibacterial ability, phosphate solubilization, and proteolytic activity from rhizomes of the Zingiberaceae family (Etlingera sp., Globba patens, Globba pendula, and Zingiber multibracteata). Nineteen bacterial isolates were obtained from Zingiberaceae rhizomes with isolate codes of EZS27, EZS18, EZS19, EZS25, EZS16, EZS08, EZS09, EZS13, EZS20, EZS14, EZS10, EZS11, EZS03, EZS05, EZS06, EZS43, EZS45, EZS47, and EZS28. The screening of the endophytes for antibacterial activity was done through the paper disc method. Four bacterial isolates presented antibacterial activities. EZS06 isolate inhibited the growth of EPEC (11 mm), P. vulgaris ATCC 13315 (10 mm), and L. monocytogenes BTCC B693 (9 mm). Also, EZS20 isolate inhibited the growth of S. aureus ATCC 29213 (17 mm), EZS28 isolate inhibited MRSA ATCC 43300 (8.6 mm), and EZS45 isolate inhibited S. Epidermidis ATCC 12228 (9 mm). The EZS19, EZS03, and EZS16 isolates dissolved the phosphate most effectively. Eight isolates (EZS19, EZS47, EZS27, EZS25, EZS09, EZS20, EZS45, and EZS06) showed the best protease activity. In general, our results showed that the endophytic bacterial strains can be used as a new and useful antibacterial agent since it showed antibacterial activity and chemical diversity. Furthermore, it also has the potential for exploitation in a wide variety of medical, agricultural, and industrial areas.